Routing Hippocampal Information Flow through Parvalbumin Interneuron Plasticity in Area CA2 - Kaoutsar Nasrallah; Ludivine Therreau; Vincent Robert; Arthur J.Y. Huang; Thomas J. McHugh; Rebecca A. Piskorowski; Vivien Chevaleyre (Cell Reports, 2019)
Summary: The hippocampus is critical for the formation of episodic memory. It is, therefore, important to understand intra-hippocampal circuitry, especially in the often overlooked area CA2. Using specific transgenic mouse lines combined with opto- and chemogenetics, we show that local plasticity of parvalbumin-expressing interneurons in area CA2 allows CA3 input to recruit CA2 pyramidal neurons (PNs), thereby increasing the excitatory drive between CA3 and CA1. CA2 PNs provide both stronger excitation and larger feed-forward inhibition onto deep, compared with superficial, CA1 PNs. This feed-forward inhibition, largely mediated by parvalbumin-expressing interneurons, normalizes the excitatory drive onto deep and superficial CA1 PNs. Finally, we identify a target of CA2 in area CA1, i.e., CA1 PNs, whose soma are located in stratum radiatum. These data provide insight into local hippocampal circuitry and reveal how localized plasticity can potentially control information flow in the larger hippocampal network. : Nasrallah et al. show how recruitment of CA2 pyramidal neurons can considerably influence CA1 output when these cells are recruited by CA3. Parvalbumin-expressing interneurons have a critical role in regulating CA2 output and normalize the excitatory drive from CA2 to CA1. In addition, CA2 strongly excites radiatum giant cells. Keywords: hippocampus, area CA2, parvalbumin-interneuron, long-term depression, disinhibition, area CA1, radiatum giant cells, delta opioid receptors